KOREKSI HUKUM ISLAM TERHADAP HUKUM JAHILIAH - Mukran H. Usman; Akhmad Hanafi Dain Yunta (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
Islamic law came to bring justice and benefit. The law of jahiliah in some cases were corrected but not removed, so this also strengthened the understanding that the sharia Law of the previous people were originated from Allah who were improved, corrected, and adjusted. This study aimed to provide an explanation and knowledge concerning the law of jahiliah that were corrected by Islamic law without being removed. The research method used was the literature study with normative approach and was supported by a historical approach. The result shows that it is clear that Islamic justice did not necessarily eradicate some of the laws of jahiliah, such as: Polygamy, dowry, and the period of idah. On the contrary, Islam eliminates the technical that are unjust and still consider that law as part of Islamic law.